2001
DOI: 10.1054/bjoc.2000.1712
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases (MMPs) in fresh human prostate tumour tissue and organ-cultured prostate tissue: Levels of collagenolytic and gelatinolytic MMPs are low, variable and different in fresh tissue versus organ-cultured tissue

Abstract: Summary Prostate tissue was obtained from 22 radical prostatectomies (performed for clinical management of prostate carcinoma) immediately after surgery. A small piece of tissue was fixed immediately in formalin and used for routine histology while a second piece was frozen in OCT and used for immuno-histochemistry. Another small piece was used for isolation of epithelial and stromal cells. The remainder of the tissue was cut into 2 × 2 mm pieces and incubated in organ culture for 8 days. In organ culture, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
2
10
2
Order By: Relevance
“…Previous work has demonstrated that MMP-1 levels in uncultured primary prostate carcinoma are very low and variable (Varani et al, 2001), whereas we have demonstrated that MMP-1 is strongly expressed in the bone metastases of prostate cancer patients. Our in vitro data also showed that in BMS co-culture, MMP-1 staining was greater in CaP co-cultures compared to BPH co-cultures.…”
Section: Discussioncontrasting
confidence: 51%
“…Previous work has demonstrated that MMP-1 levels in uncultured primary prostate carcinoma are very low and variable (Varani et al, 2001), whereas we have demonstrated that MMP-1 is strongly expressed in the bone metastases of prostate cancer patients. Our in vitro data also showed that in BMS co-culture, MMP-1 staining was greater in CaP co-cultures compared to BPH co-cultures.…”
Section: Discussioncontrasting
confidence: 51%
“…Among the proteases that have been most studied in primary cultures are matrix metalloproteinases (MMPs). Varani et al (2001) placed normal prostatic epithelial and stromal cells into culture for 2 days, then evaluated enzymatic activity of MMPs in the conditioned media. They found that stromal cells secreted MMP-2, whereas epithelial cells secreted both MMP-2 and MMP-9.…”
Section: Adhesion Invasion and Migration Of Cancer Cellsmentioning
confidence: 99%
“…Also the expression of MMP-9 and MMP-2 in benign and malignant prostate tissue is documented. 13,14 Correlation between MMP expression and clinical parameters is rare. The activity of MMPs is regulated by gene transcription, 15 activation of the proenzymes 16 and inhibition of the activated proteinases by different inhibitors.…”
Section: Introductionmentioning
confidence: 99%